Empirical Investigation of Customers’ Channel Extension Behavior: Moving from Offline Channel to Online Channel Under the Umbrella of Satisfaction - WASEEM AHMAD KHAN; Muhammad Rizwan; MUHAMMAD SALMAN AZHAR; SHAKEEL SARWAR (International Journal of Business and Economic Affairs, 2021)
The phenomenon of online shopping experienced remarkable progress because of its unique benefits for customers. These benefits include time convenience, reduce travelling costs, low overhead expenditures, get rid of physical store visits, a wide range of products and services, and many others. The current study aimed to understand the customers repurchase behavior in a multichannel environment. The study contributes to provide guidelines to the firms and managers to understand how customers behave in multiple channels, how firms and customers better interact in a multichannel environment, and how these multichannel firms can enhance the online repurchase intentions among Pakistani fashion industry customers. The data was collected from various online customers of fashion related products. The techniques used to collect and analyzes data was PLS algorithm and bootstrapping. Further, online satisfaction is associated with online repurchase intentions. Therefore, the online satisfaction proved to be important attribute to convince the customers for repurchase. Based on these results, the assumption is intuitively strong that satisfaction is associated with customers’ potential future decisions (repeat purchases and revisiting) and empirically verified by the current study. Hence, online satisfaction is an influential factor for customers’ future decisions for buying again from the same channel.